Training, Job Security and Incentive Wages - Margarita Katsimi (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper considers the optimal level of firm-specific training by taking into account the positive effect of training on the expected duration of workers' current employment. In the framework of an efficiency wage model, a short expected job tenure represents a disamenity that reduces the penalty from shirking. As this disamenity increases, workers have an incentive to continue providing a positive level of effort only if they are compensated by a higher wage. We endogenize the employment separation rate by introducing firm-specific training. Firm-specific training creates a rent that is lost if the worker is separated from the firm. As a result, the firm will be more reluctant to fire its trained workforce in a recession. This implies that firm-specific training can decrease current wages as it implies a credible commitment to lower future labour turnover.
Keywords: 330; efficiency wages; firm-specific training